2022
DOI: 10.52628/88.2.9683
|View full text |Cite
|
Sign up to set email alerts
|

Radial tuberosity anatomy in intramedullar repair of distal biceps tendon ruptures. A radiological study

Abstract: The aim of this study was to measure cortex thickness and medullar canal width of the bicipital tuberosity, to evaluate the accessibility of a intramedullar fixation device and the resistance to pullout strengths of the anterior cortex. The final objective was to determine the length of tendon ingrowth size that will be expected when using this surgical technique. A total of 144 computer tomography images of the proximal radius were used. Bone thickness of the anterior and posterior cortex and medullar canal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Comparison with other data on minimally invasive DBT repairs is limited by a paucity of literature on this type of repair, and due to the relatively low number of cases in the published literature. Although a number of authors describe surgical techniques or cadaveric studies [ 10 , 22 , 25 , 26 ], few studies have reported patient outcomes of minimally invasive or endoscopically-assisted DBT repairs. Sharma and MacKay [ 19 ] described two endoscopic repairs using an Endobutton in 2005 and reported no complications for either case.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with other data on minimally invasive DBT repairs is limited by a paucity of literature on this type of repair, and due to the relatively low number of cases in the published literature. Although a number of authors describe surgical techniques or cadaveric studies [ 10 , 22 , 25 , 26 ], few studies have reported patient outcomes of minimally invasive or endoscopically-assisted DBT repairs. Sharma and MacKay [ 19 ] described two endoscopic repairs using an Endobutton in 2005 and reported no complications for either case.…”
Section: Discussionmentioning
confidence: 99%